A network analysis of miRNA mediated gene regulation of rice: crosstalk among biological processes1. Issue 8 (14th August 2015) - Mal, Chittabrata; Deb, Arindam; Aftabuddin, Md.; Kundu, Sudip
<x xml:space="preserve">Abstract</x> Modules of miRNAs' co-targeting and co-functional network of rice identify miRNAs co-regulating target genes having several interrelated biological processes.